Intellectual Capital Management as a Strategic Asset of Higher Education in Improving Organizational Performance - Istikhoroh, Siti; Lasiyono, Untung; Sukandani, Yuni (KnE Social Sciences, 2024)
Higher education involves various kinds of science that develops and produces reliable human resources in the field of science. Higher education performance is primarily determined by the leadership’s ability to manage knowledge-based strategic assets, namely intellectual capital. This research designs all elements that form intellectual capital, such as human capital, structural capital, and relational capital, in one model according to their organizational function. The research aims to optimize the role of intellectual capital as a strategic asset for higher education to improve organizational performance. This is a survey research, where data were obtained by distributing questionnaires to higher education leaders in Surabaya, both State Higher Education (SHE) and Private Higher Education (PHE). The research produced a model for managing intellectual capital, where human capital and structural capital are independent variables for higher education performance. In contrast, relational capital is a mediator for both. The research results can guide higher education leaders in managing intellectual capital as a strategic asset determining organizational performance. Keywords: human capital, structural capital, relational capital, organizational performance